The Effect of Embryo Transfer Process Duration on Implantation Success - Kasapoglu, Isıl; Aslan, Kiper; Orhan, Adnan; Albayrak, Ozge; Haskoylu, Seyma; Kuspinar, Goktan; Avcı, Berrin; Uncu, Gürkan (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: To evaluate the effect of the embryo transfer duration of standard and simple embryo transfer method. STUDY DESIGN: This study was a retrospective cohort study conducted at a tertiary ART Centre, between June 2018- September 2018. Day 5 fresh embryo transferred patients aged between 18 - 40, BMI <35 kg/m2 without uterine pathology were enrolled in the study. Patients were divided into two groups. Group-1 consisted of patients who had successful implantation and Group-2 consisted of patients who did not have implantation. Groups were compared according to their embryo transfer durations. Ninety-two patients were enrolled in the study. Also, sub-steps of as; cleaning of the cervical mucus and placing the outer catheter in the cervix, loading the embryo to the catheter, the period between embryo loading and embryo transfer, and following that, time spent for retracting the outer catheter evaluated. RESULTS: Between Group-1 and Group-2, there was no significant difference for the period of cervical cleaning and placing the outer catheter into the cervix (Respectively; 63 sec vs. 76 sec; p=0.18), the period of embryo loading (Respectively; 69sec vs. 71sec; p=0.46), the period between embryo loading and embryo transfer (Respectively; 10 sec vs. 10 sec; p=0.74, retracing the outer catheter (Respectively; 25.5sec vs. 24sec; p=0.42 and the total period of embryo transfer (182sec vs. 182.5 sec; p=0.55). CONCLUSION: The embryo transfer duration is not related to implantation rates. The duration of the embryo transfer process steps is not a distinguishing factor if a good-quality embryo transfer is done.